The house on Via Gemito - Starnone, Domenico, 1943- (Europa Editions, 2023)
A modest apartment in Via Gemito smelling of paint and turpentine. Its furniture pushed up against the wall to create a make-shift studio. Drying canvases moved from bed to floor each night. Federí, the father, a railway clerk, is convinced that he possesses great artistic promise. If it weren't for the family he must feed and the jealousy of his fellow Neapolitan artists, nothing would stop him from becoming a world-famous painter. Ambitious and frustrated, genuinely talented but also arrogant and resentful, Federí is scarred by constant disappointment. He is a larger-than-life character, a liar, a fabulist, and his fantasies shape the lives of those around him, especially his young son, Mimi, short for Domenico, who will spend a lifetime trying to get out from under his father's shadow. --from Amazon.